Sustainable Work Engagement: The Role of Work-Life Balance, Organizational Support, and Mental Well-Being (A Systematic Review) - Nugroho, Johanes Aji; Riyanto, Setyo; Suprapto, Suprapto; Herminingsih, Anik (Research Center and Case Clearing House PPM School of Management, 2026)
This study aims to synthesize empirical evidence on how Work–Life Balance (WLB) and Perceived Organizational Support (POS) sustain work engagement through mental well-being as a mediating mechanism. Following PRISMA 2020, a Boolean search across Scopus yielded 1,339 records; after systematic screening, 165 peer-reviewed articles (2020–2026) were included. Analysis reveals three key findings: (1) mental well-being is predominantly operationalized through deficit indicators (burnout, stress) rather than positive capacities (resilience, flourishing); (2) cross-sectional designs dominate, undermining temporal validity of